2013
DOI: 10.1007/s12265-013-9506-8
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Dose-Dependently Potentiates the Pro-inflammatory Activity of Lipopolysaccharide Both In Vitro and In Vivo

Abstract: Since contradictory findings have been reported on potential effects of statins in modulating the inflammatory response, we have analysed the biological activity of lovastatin both in vitro using the Raw 264.7 murine macrophagic cell line and in vivo using BALB/c mice. When added to Raw 264.7 cells in combination with lipopolysaccharide, lovastatin significantly potentiated the release of interleukin-1β, interleukin-6 and interleukin-12 with respect to lipopolysaccharide alone and showed an additive effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Hence, we investigated the influence of XZK and its fractions under the conditions of inflammation. Lv exhibited a small proinflammatory effect, which was identical to that reported in current studies [45]. However, XZK and its fraction 1, F1, could suppress the expression of inflammatory factors, compared to the TNF-α and LPS groups (Fig.…”
Section: Hfd Decreased the Conversion Of LV Into Lvasupporting
confidence: 87%
“…Hence, we investigated the influence of XZK and its fractions under the conditions of inflammation. Lv exhibited a small proinflammatory effect, which was identical to that reported in current studies [45]. However, XZK and its fraction 1, F1, could suppress the expression of inflammatory factors, compared to the TNF-α and LPS groups (Fig.…”
Section: Hfd Decreased the Conversion Of LV Into Lvasupporting
confidence: 87%
“…All fermentation experiments in this study for MK production were maintained for 14 days, except for monitoring of fermentation process. Two-stage fermentation was used and the temperature Medium volume (mL) 30 70 X 6 Inoculum size (%) 8 12 X 7 Inoculum culture time (h) 24 36 X 8 Fermentation temperature (°C) a) 22 28 X 9 Fermentation time at 30°C (days) 2 4 a) Temperature used for second-stage fermentation after fermentation at 30°C.…”
Section: Optimization Of Fermentation Conditions For Mk Productionmentioning
confidence: 99%
“…Coronary heart disease, which is often triggered by hypercholesterolemia, is a leading cause of death around the world [1][2][3]. Therefore, lovastatin (also named mevinolin or mevacor), which is a hypocholesterolemic agent commonly manufactured by Aspergillus terreus [4], was successfully developed and widely used over the past 30 years throughout the world [5,6]. However, lovastatin produced by A. terreus is normally used as a clinical drug because the strain is not generally recognized to be safe [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Increased concentrations or expression of the pro-inflammatory cytokine IL-1b has been found in airway cells of patients with asthma [26e28]. Although lovastatin has been reported to potentiate the pro-inflammatory activity of lipopolysaccharide in a murine macrophage cell line and in vivo in mice [29], we found that treatment with atorvastatin plus ICS compared to ICS alone reduced sputum concentration of IL-1b in asthma. IL-7 positive staining cells are increased in patients with COPD and healthy smokers compared with healthy non-smokers [30] and in smokers with asthma we found that improvements in asthma control scores with atorvastatin and ICS were associated with a decrease in sputum IL-7 concentrations.…”
Section: Discussionmentioning
confidence: 49%